Pengaruh Latihan Menggunakan Metode Target terhadap Shooting Sepak Bola pada Siswa Kelas 4 SD Negeri 4 Srikaton (International Forum of Researchers and Lecturers, 2025)
Some students still it difficult to school at the target corretly. Toovercome this, one of them can be given target game treatment. This study aims to determine the effect of target play on shooting skills in soccer games in special sports class students at SD Negeri 4 Srikaton. This research is a type of experimental research one grup pretest-posstest design with 12 treatments. The subjects of this study were 23 students of SD Negeri 4 Srikaton. Shootingability is measured using the Bobby Charloton instrument proposed by Danny Mielke (2007 : 76). Based on the analysis of the result of the researsch and discussion, it was found that the T value of significance was 0.01 or less that 0.05, so there was already a significant difference. The mean value of the pretest results was 82.61, while the accuracy of the posstest increased to 115.56. Thus it can be concluded that the hypothesis is accepted, meaning that there is an effect of target play on shooting skills in soccer games for special sports class students at SD Negeri 4 Srikaton.